2015
DOI: 10.46743/2160-3715/2012.1708
|View full text |Cite
|
Sign up to set email alerts
|

African American Women: The Face of HIV/AIDS in Washington, DC

Abstract: In 2007, the estimated HIV and AIDS case rates among adult and adolescent African-American females in the United States was 60.6 per 100,000, as compared to 3.3 per 100,000 for adult and adolescent white American females. Women living with HIV or AIDS often face complex social problems that may inhibit them from accessing resources and healthcare services to assist them in coping with the disease. In-depth interviews and direct observations utilizing open-ended note taking were conducted at an HIV service prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous research has found that sexual scripts for Black women imposed male dominating ideals such as satisfying men's physical desires, reproducing children, and being the moral gatekeepers for their communities (Bowleg et al, 2004). Many of these gendered norms manifest as relationship preferences and acceptance of multiple concurrent relationships that may increase HIV infection susceptibility (Amutah, 2012). Such perceptions of masculinity and femininity has been shown to be disruptive to the usage of contraceptives and other risk-avoiding activities (Paxton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that sexual scripts for Black women imposed male dominating ideals such as satisfying men's physical desires, reproducing children, and being the moral gatekeepers for their communities (Bowleg et al, 2004). Many of these gendered norms manifest as relationship preferences and acceptance of multiple concurrent relationships that may increase HIV infection susceptibility (Amutah, 2012). Such perceptions of masculinity and femininity has been shown to be disruptive to the usage of contraceptives and other risk-avoiding activities (Paxton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…8,10,45 Understanding the Lived Experiences of BWLWH In general, BWLWH face a myriad of structural inequities relevant to their families' reproductive well-being, including-but not limited to-lack of access to childcare, health information, transportation, and stable and safe housing, as well as barriers associated with substance use and related recovery. 10,47 As such, ethical research engagement with BWLWH and other marginalized groups requires creating empowering and reflective spaces and structures that allow individuals and groups to share their stories, reframe existing narratives, and minimize the power dynamics that traditionally exist between researchers and participants. 48 Similarly, to bolster trust, rapport, respect, and transparency between clinicians and patients, developing innovative health care models and frameworks that give consideration to the complex medical and social needs of medically underserved populations is an ethical imperative.…”
Section: Reproductive Autonomymentioning
confidence: 99%